Pricing Strategies and Financial Performance: The Mediating effect of Competitive Advantage. Empirical Evidence from Uganda, A study of Private Primary Schools (Global Journal of Management and Business Research, 2019)
The purpose of this study was to examine the mediating effect of Competitive advantage on the relationship between Pricing strategies and Financial performance in private primary schools of Uganda. - The research adopted the Med Graph program and Sobel tests for the mediation effects so as to develop a closed loop model of financial performance of private primary schools. The study is based on a quantitative approach and cross sectional Research design. Descriptive statistics and inferential statistics were used in the analysis. The results reveal that that competitive advantage partially mediates the relationship between pricing strategies and financial performance (partial mediation). This study makes a contribution by providing information that is relevant for filling the practical gap that exists in financial performance of private primary schools in the settings of developing countries as well as contributing to the theoretical development of pricing strategies. Practical implications of this paper puts it that in order to have a meaningful interpretation of the results of the relationships between study variables, it is always vital to assess the role of the mediator in the relationship. This enables practitioners and scholars to comprehend and make legitimate decisions and conclusions that can foster enhanced financial performance of private primary schools.
Keywords: pricing strategies; competitive advantage; financial performance; primary schools